Exploring The Slang Word Formation Processes Found in Girlboss Tv Series - Areta Tirza Partadarsana; Josefa Juniarti Mardijono (Kata Kita: Journal of Language, Literature, and Teaching, 2022)
The purpose of this study was to investigate the formation of slang words used by Sophia, the main character of the Girlboss TV Series. The writer conducted this study to determine the types of word formations formed in Sophia's slang words in each episode and the morphological processes involved in the creation of those slang words. Additionally, this study was carried out in a qualitative approach. The writer used the theory of word formation and morphology by Yule (2020) in her study. The findings revealed that compounding, blending, clipping, coinage, acronyms, derivation, and multiple processes were all used in the formation of slang words used by the main character in the Girlboss. Meanwhile, borrowing, backformation, hypocorism, and conversion were not found in the data analysed. Based on their respective origin words and the theory of the types of word formation processes, the slang words that appear in these 11 episodes are divided into several different types of word formation. In short, it showed that the main character of Girlboss TV series often uses slang when communicating with their peers, some of which are in the form of abbreviations, modified elements from original words, and some use new words.